Binding of Aflatoxin B1 to Lactobacillus paracasei SNP-2 and Stability of Bacteria-AFB1 Complex - Rohula Utami; Tyas Utami; Suparmo Suparmo; Endang Sutriswati Rahayu (Indonesian Food and Nutrition Progress, 2017)
The aim of this research was to study the binding ability of viable and non-viable of Lactobacillus paracasei SNP-2 to aflatoxin B1 (AFB1) in phosphate buffer saline (PBS) at pH 7.3. Bacterial cells were grown in MRS broth at 37 °C for 24 h, and then centrifuged at 1,800g[a1]  for 20 min at 10 °C to get the pellet. Pellet was suspended in PBS pH 7.3 until the cell concentration was about 1010 CFU/ml. Viable cells, the heated, and acid-killed cells were evaluated their ability to bind AFB1 in PBS pH 7.3. Stability of the L. paracasei SNP-2/AFB1 complexes was evaluated by determining the amount of the released AFB1 to the PBS following five times washing. The results showed that AFB1 binding ability to heat-and acid-kill bacteria were higher than that of by viable cells. More than 70% of bound AFB1 was released from viable bacteria after five times washing. However, the heated and acid-killed cell treatments significantly increased the complex stability of bacteria-AFB1